Alcohol Use and Alcohol-Related Seizures in Patients With Epilepsy - Hamerle, Michael; Ghaeni, Leyli; Kowski, Alexander; Weissinger, Florian; Holtkamp, Martin (Frontiers in Neurology, 2018)
Purpose: This study aimed to assess alcohol consumption and the occurrence of alcohol-related seizures in patients with epilepsy within the last 12 months. Methods: In an epilepsy outpatient clinic, a standardized questionnaire was used to collect data retrospectively from consecutive adult epilepsy patients who had been suffering from the disease for at least 1 year. Logistic regression analyses were performed to identify independent predictors. Results: A total of 310 patients with epilepsy were included. Of these, 204 subjects (65.8%) consumed alcohol within the last 12 months. Independent predictors for alcohol use were antiepileptic drug monotherapy (OR 1.901) and physicians' advice that a light alcohol intake is harmless (OR 4.102). Seizure worsening related to alcohol consumption was reported by 37 of the 204 patients (18.1%) who had used alcohol. All 37 subjects had consumed large quantities of alcohol prior to the occurrence of alcohol-related seizures regardless of their usual alcohol-drinking behavior. The amount of alcohol intake prior to alcohol-related seizures was at least 7 standard drinks, which is equivalent to 1.4 L of beer or 0.7 L of wine. In 95% of cases, alcohol-related seizures occurred within 12 h after cessation of alcohol intake. Independent predictors for alcohol-related seizures were generalized genetic epilepsy (OR 5.792) and chronic heavier alcohol use (OR 8.955). Conclusions: Two-thirds of interviewed subjects had consumed alcohol within the last 12 months. This finding may be an underestimate due to patients' self-reporting and recall error. In all cases, the occurrence of alcohol related-seizures was associated with timely consumption of considerably large amounts of alcohol. Thus, a responsible alcohol intake seems to be safe for most patients with epilepsy. However, subjects with epilepsy and especially those with generalized genetic epilepsy should be made aware of an increased risk for seizures related to heavy alcohol consumption. Factors accompanying acute heavy alcohol intake such as altered sleep architecture, impaired adherence to antiepileptic medication, and metabolic disturbances may further facilitate the occurrence of seizures.